Piecemeal Policy in the Theory of Second Best - Davis, O. A.; Whinston, A. B. (Review of Economic Studies, 1967)
Journal Article Piecemeal Policy in the Theory of Second Best Get access O. A. Davis, O. A. Davis Carnegie Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar A. B. Whinston A. B. Whinston Purdue University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 3, July 1967, Pages 323–331, https://doi.org/10.2307/2296681 Published: 01 July 1967